Extended follow-up of a phase 2 trial of xevinapant plus chemoradiotherapy in high-risk locally advanced squamous cell carcinoma of the head and neck: a randomised clinical trial. (April 2023) - TAO, Yungan; Sun, Xu-Shan; Pointreau, Yoann; Le Tourneau, Christophe; Sire, Christian; Kaminsky, Marie-Christine; Coutte, Alexandre; Alfonsi, Marc; Calderon, Benôit; Boisselier, Pierre; Martin, Laurent; Miroir, Jessica; et al.
Abstract: Introduction: We report long-term efficacy and overall survival (OS) results from a randomised, double-blind, phase 2 study (NCT02022098) investigating xevinapant plus standard-of-care chemoradiotherapy (CRT) vs. placebo plus CRT in 96 patients with unresected locally advanced squamous cell carcinoma of the head and neck (LA SCCHN). Methods: Patients were randomised 1:1 to xevinapant 200 mg/day (days 1–14 of a 21-day cycle for 3 cycles), or matched placebo, plus CRT (cisplatin 100 mg/m 2 every 3 weeks for 3 cycles plus conventional fractionated high-dose intensity-modulated radiotherapy [70 Gy/35 F, 2 Gy/F, 5 days/week for 7 weeks]). Locoregional control, progression-free survival, and duration of response after 3 years, long-term safety, and 5-year OS were assessed. Results: The risk of locoregional failure was reduced by 54% for xevinapant plus CRT vs. placebo plus CRT but did not reach statistical significance (adjusted hazard ratio [HR] 0.46; 95% CI, 0.19–1.13; P = .0893). The risk of death or disease progression was reduced by 67% for xevinapant plus CRT (adjusted HR 0.33; 95% CI, 0.17–0.67; P = .0019). The risk of death was approximately halved in the xevinapant arm compared with placebo (adjusted HR 0.47; 95% CI, 0.27–0.84; P = .0101). OS was prolonged with xevinapant plus CRT vs. placebo plus CRT; median OS not reached (95% CI, 40.3-not evaluable) vs. 36.1 months (95% CI, 21.8–46.7). Incidence of late-onset grade ≥3 toxicities was similar across arms. Conclusions: In this randomised phase 2 study of 96 patients, xevinapant plus CRT demonstrated superior efficacy benefits, including markedly improved 5-year survival in patients with unresected LA SCCHN. Graphical abstract: Image 1 Highlights: Xevinapant + CRT improved PFS after 3 years of follow-up The risk of death was more than halved in the xevinapant arm compared with placebo The incidence of late-onset grade ≥3 toxicities was similar across treatment groups